PENGARUH WITER PROFESIONAL DALAM MENINGKATKAN KUALITAS PELAYANAN DI RESTORAN HARRIS CAFÉ HARRIS RESORT WATERFRONT HOTEL BATAM - ", Zulkifli; Achnes, Syofia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study aims to determinesthe effect of the waiter Professional in improving the quality of service at Harris Cafe Restaurant Harris Resort Waterfront Hotel Batam. This research was conducted at the Harris Resort Waterfront Hotel Batam street Marina Waterfront, JalanKyai Haji Ahmad Dahlan, Batam, Riau Islands. The population was taken to the consumers who eat and drink in restaurants Harris Café Harris Resort Waterfront Hotel Batam in May to June 2016. The respondents numbered was 100 people who eat and drink in the restaurant Harris Café Harris Resort Waterfront Hotel Batam. Variable knowledge, respond, skill and attitude is partially affected the quality of service at Cafe Harris Resort Waterfront Hotel Batam. Variable knowledge, response, skill and attitude simultantly influences the quality of service at Cafe Harris Resort Waterfront Hotel Batam. The analysis showed that 71.8% change in the value of the dependent variable quality of service (Y) is affected by the variable knowledge, respond, skill and attitude. The rest 28.2% change in the value of the dependent influenced by other variables that are not in this study.Keywords : Waiter Professional, quality of service, knowledge, response, skill and attitude